Design and analysis of interbody fusion cage materials based on finite element analysis - Nur Ariza Hayani, Mohd Nizam; Muhammad Hazli, Mazlan; Nur Saliha, Md Salleh; Muhammad Anas, Razali; Abdul Halim, Abdullah; Muhammad Hilmi, Jalil; Takano, Hiromitsu; Nur Dalilah Diyana, Nordin (Institute of Electrical and Electronics Engineers Inc., 2021)
This study investigates the effect of the Posterior Lumbar Interbody Fusion (PLIF) cage's material on the strength and stability of the cage. The lumbar vertebrae L2-L3 unit finite element model was developed from computed tomography (CT) scan images in 3D Slicer software. The PLIF cage model was constructed using Solidworks software. The models were assigned with polyetheretherketone (PEEK) and polylactic acid (PLA) materials. The models were implanted and analyzed in Ansys Workbench Software by applying external preload, compression load and other load conditions to mimic the spine physiological motions under static and dynamic analysis. The von Mises stress and maximum principal stress were observed and analyzed to evaluate their strength and stability. In addition, the percentage differences between the von Mises stress and yield strength of the material and between the maximum principal stress and critical strength of the material were calculated. The PEEK cage produced higher von Mises stresses than the PLA cage for the static analysis. However, the PEEK cage exhibited lower percentage differences than the PLA cage. This result indicates that the PEEK cage has the superior structural integrity to the PLA interbody cage. The results from the dynamic analysis showed that both cages exhibited extremely low von Mises stresses and similar curve patterns. These results indicate that both cages are stable and do not pose harmful health implications. Thus, PLA can be considered an alternative material for the cage because it is more cost-effective than the PEEK material, and stresses generated were far lower than the ultimate tensile strength and yield strength of the material.